Identification and Characterisation CRN Effectors in Phytophthora capsici Shows Modularity and Functional Diversity. - Remco Stam (Public Library of Science (PLoS), 2013)
Phytophthora species secrete a large array of effectors during infection of their host plants. The Crinkler (CRN) gene family encodes a ubiquitous but understudied class of effectors with possible but as of yet unknown roles in infection. To appreciate CRN effector function in Phytophthora, we devised a simple Crn gene identification and annotation pipeline to improve effector prediction rates. We predicted 84 full-length CRN coding genes and assessed CRN effector domain diversity in sequenced Oomycete genomes. These analyses revealed evidence of CRN domain innovation in Phytophthora and expansion in the Peronosporales. We performed gene expression analyses to validate and define two classes of CRN effectors, each possibly contributing to infection at different stages. CRN localisation studies revealed that P. capsici CRN effector domains target the nucleus and accumulate in specific sub-nuclear compartments. Phenotypic analyses showed that few CRN domains induce necrosis when expressed in planta and that one cell death inducing effector, enhances P. capsici virulence on Nicotiana benthamiana. These results suggest that the CRN protein family form an important class of intracellular effectors that target the host nucleus during infection. These results combined with domain expansion in hemi-biotrophic and necrotrophic pathogens, suggests specific contributions to pathogen lifestyles. This work will bolster CRN identification efforts in other sequenced oomycete species and set the stage for future functional studies towards understanding CRN effector functions.